Central Opioidergic System Interplay with Histamine on Food Intake in Neonatal Chicks: Role of µ-Opioid and H1/H3 Receptors - Jaefari-Anari,M (2018)
ABSTRACT The present study was designed to examine the role of Opioidergic and Histaminergic systems on feeding behavior in 3-hour food deprived neonatal meat- type chicks. In experiment 1, chicks received intracerebroventricular (ICV) injection of (A) control solution, (B) α-FMH (alpha fluoromethyl histidine; 250 nmol), (C) DAMGO (µ-opioid receptor agonist, 125 pmol) and (D) α-FMH + DAMGO. Experiments 2-4 were similar to experiment 1, except chicken ICV injected with Chlorpheniramine (histamine H1 receptors antagonist; 300 nmol), famotidine (histamine H2 receptors antagonist; 82 nmol) and Thioperamide (histamine H3 receptors antagonist; 300 nmol) instead of the α-FMH. In experiments 5-8, birds ICV injected with the same procedure as experiments 1-4, except they were injected with DPDPE (δ-opioid receptor agonist, 40 nmol) instead of DAMGO. Experiments 9-12 were similar to the experiments 1-4, except neonatal broilers ICV were injected with U-50488H (κ-opioid receptor agonist, 30 nmol) instead of DAMGO. Then the cumulative food intake was measured until 120 min post injection. According to the results, ICV injection of DAMGO, significantly decreased food intake (p<0.05) while DPDPE and U-50488H increased feeding behavior compared to the control group (p<0.05). Co-administration of the α-FMH and DAMGO significantly inhibited hypophagic effect of the DAMGO in neonatal broilers (p<0.05). Also, Chlorpheniramine significantly inhibited DAMGO- induced feeding behavior in neonatal chicks (p<0.05). In addition, co-administration of the Thioperamide + DAMGO significantly amplified the hypophagic effect of the DAMGO in neonatal chicks (p<0.05). However, famotidine had no effect on food intake induced by DAMGO (p>0.05). Also, the hyperphagic effect of DPDPE and U-50488 had no affect by α-FMH, Chlorpheniramine, famotidine and Thioperamide (p>0.05). These results suggested that an interconnection between central opioidergic and histaminergic systems on feeding behavior is mediated via µ-opioid and H1/H3 receptors in neonatal broilers.